A Critical Analysis of Causation Rules in Marine Insurance - Bima Manopo; Robert Merkin QC (BESTUUR, 2021)
The United Kingdom has regulated Marine Insurance in great detail in some laws and regulations, but these regulations do not seem to have been fully implemented. This study will discuss the Causation Rules in Marine Insurance. More specifically, this article has looked at the impact of the development of the causation rules in marine insurance after implementing MIA 1906. This study argues that the efficiency test is now be regarded as a historical precedent of the causation rules. What is clear is that the operation of the efficiency test alters the rule which previously relied on a question of law by looking at the latest cause of the loss to recognize a question of fact by measuring the most predominant cause of the loss. However, it does not mean that the newest cause of the loss is automatically disregarded. An immediate cause may be proximate if it has an efficient and predominant effect to cause the loss.